Limnology of two freshwater ponds of Imphal, Manipur - Gupta, M Das (Indian Journal of Fisheries, 2011)
Our knowledge on the limnology of the ponds of the North-Eastern India, specially Manipur, is rather poor. The present study has been undertaken to know the seasonal variations in the abiotic condition and also to know the biological condition of 2 ponds of Manipur.